Estudo da eletrodeposição de zinco e índio em meio de cloreto de colina e etilenoglicol sobre superfície de aço carbono 1020 - Oliveira, José Joelson Pires (2020)
Zinc and Zinc-rich alloys are materials widely used in the coatings industry, being the subject of study by several research groups in electrochemistry. In this work, electrochemical, thermodynamic and structural results obtained from the study of the electrodeposition of Zinc and Indium in eutectic solvent are presented, which was formed by a mixture of 1: 2 molar ratio between choline chloride and ethylene glycol. Platinum sheet, silver wire coated with silver chloride immersed in the eutectic solvent itself and carbon steel disc were used, respectively, as auxiliary electrodes, pseudo-reference and work. Cyclic voltammeters were performed varying several parameters, such as composition of the electrolytic bath, inversion potential and scan rate. The electrolyte was formed by 0.4 mol L–1 of ZnCl2, different concentrations of InCl3 (from 0 to 50 × 10–3 mol L–1) and different water contents (from 0 to 10 %). The values ​​of the diffusion coefficient of the Zn2+ and In3+ species at different temperatures, as well as the values ​​of viscosity and specific gravity for the electrolytes of interest, were determined. Using an Arrhenius-type equation, it was possible to estimate the activation energy for the diffusion of Zn2+ and In3+ ions, namely 58.09 kJ mol–1 e 31.31 kJ mol–1, respectively. Electrodeposits were obtained potentiostatically at –1.2 V with a charge density of –3 C cm–2. The obtained coatings were then subjected to electrochemical galvanostatic stripping, which allowed to estimate the thickness, faradic efficiency and to quantify the percentages of electroplated Zinc and Indium. Structural characterizations were also made regarding the morphology, composition and crystalline structure of the electrodeposits, using, respectively, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction. The results indicated favoring of the zinc electrodeposition with the increase of the working temperature and with the increase of the percentage of water added to the electrolyte. The electrodeposition of Indium was favored by increasing the concentration of In3+ in the electrolyte and increasing of the rotation rate of the electrode.